Divergent Synthesis of Ultrabright and Dendritic Xanthenes for Enhanced Click‐Chemistry‐Based Bioimaging. Issue 5 (7th December 2022) - Montiel, Luis; Spada, Fabio; Crisp, Antony; Serdjukow, Sascha; Carell, Thomas; Frischmuth, Thomas
Abstract: Biorthogonal labelling with fluorescent small molecules is an indispensable tool for diagnostic and biomedical applications. In dye‐based 5‐ethynyl‐2′‐deoxyuridine (EdU) cell proliferation assays, augmentation of the fluorescent signal entails an overall enhancement in the sensitivity and quality of the method. To this end, a rapid, divergent synthetic procedure that provides ready‐to‐click pH‐insensitive rhodamine dyes exhibiting outstanding brightness was established. Compared to the shortest available synthesis of related high quantum‐yielding rhodamines, two fewer synthetic steps are required. In a head‐to‐head imaging comparison involving copper(I)‐catalyzed azide alkyne cycloaddition reactions with in vitro administered EdU, our new 3, 3‐difluoroazetidine rhodamine azide outperformed the popular 5‐TAMRA‐azide, making it among the best available choices when it comes to fluorescent imaging of DNA. In a further exploration of the fluorescence properties of these dyes, a set of bis‐MPA dendrons carrying multiple fluorescein or rhodamine units was prepared by branching click chemistry. Fluorescence self‐quenching of fluorescein‐ and rhodamine‐functionalized dendrons limited the suitability of the dyes as labels in EdU‐based experiments but provided new insights into these effects. Abstract : A rapid and divergent synthetic route that provides ready‐to‐click pH‐insensitive rhodamine dyes exhibiting outstanding brightness was developed. In EdU cell proliferation assays, our 3, 3‐difluoroazetidine rhodamine azide outperformed the popular 5‐TAMRA‐azide. A set of bis‐MPA dendrons carrying multiple fluorescein or our rhodamine revealed self‐quenching effects, suggesting potential application as FRET quenchers.